Talent identification and deliberate programming in skeleton: Ice novice to Winter Olympian in 14 months - Bullock, N.; Gulbin, J. P.; Martin, D. T.; Ross, A.; Holland, T.; Marino, F. (Journal of Sports Sciences, 2009)
The aims of this study were to talent transfer, rapidly develop, and qualify an Australian female athlete in the skeleton event at the 2006 Torino Winter Olympic Games and quantify the volume of skeleton-specific training and competition that would enable this to be achieved. Initially, 26 athletes were recruited through a talent identification programme based on their 30-m sprint time. After attending a selection camp, 10 athletes were invited to undertake an intensified skeleton training programme. Four of these athletes were then selected to compete for Australia on the World Cup circuit. All completed runs and simulated push starts were documented over a 14-month period. The athlete who eventually represented Australia at the Torino Winter Olympic Games did so following approximately 300 start simulations and about 220 training/competition runs over a period of 14 months. Using a deliberate programming model, these findings provide a guide to the minimum exposure required for a novice skeleton athlete to reach Olympic representative standard following intensified sport-specific training. The findings of this study are discussed in the context of the deliberate practice theory and offer the term "deliberate programming" as an alternative way of incorporating all aspects of expert development.